Transcriptional Programs Underlying Cold Acclimation of Common Carp (Cyprinus carpio L.) - Long, Yong; Li, Xixi; Li, Fengyang; Ge, Guodong; Liu, Ran; Song, Guili; Li, Qing; Qiao, Zhigang; Cui, Zongbin (Frontiers in Genetics, 2020)
Properly regulated transcriptional responses upon environmental perturbations are important for fitness of fish. Although gene expression profiles in tissues of common carp upon cold stress were previously characterized, effects of genetic diversity on hypothermia-elicited transcriptional regulations remain unclear. The cold tolerance of three common carp strains, including Hebao red carp, Yellow river carp and Songpu mirror carp, was significantly enhanced after acclimation to a mild hypothermia stress at 18 oC for 24 h, based on measurement of their critical thermal minimum (CTMin). Gene expression profiles of the brain and heart from different strains under both control and cold-acclimated conditions were characterized with RNA-sequencing. The comparative analyses identified common cold-responsive genes (CRGs) and alternative splicing (AS) events across the strains. Meanwhile, a large number of strain-specific CRGs and cold-induced AS events were detected, indicating substantial effects of genetic diversity on the transcriptional responses to cold stress. Consistent with the enrichment of the steroid and cholesterol biosynthetic processes within up-regulated genes in brain of all the strains, total cholesterol content in the brain of Songpu mirror carp was significantly increased upon cold stress. Moreover, cold-induced AS of a splicing factor gene, rbmx (RNA-binding motif protein, X chromosome) was confirmed by real-time quantitative PCR. These results defined the core genetic programs that are important for cold acclimation and offered valuable clues for investigating the molecular mechanisms underlying cold acclimation of fish.